The impact of ICT on regional economic growth: Empirical evidence from 34 provinces of Indonesia - Yudi Adhi Purnama; Hitoshi Mitomo (International Telecommunications Society (ITS), 2018)
Rapid ICT development in recent decades has attracted substantial consideration from academia. Moreover, many studies suggest the advancement of mobile technology has the substantial effect on development, especially in developing countries. Despite the massive adoption of mobile communication, there is a sparse study on emerging economy. Furthermore, Indonesia as a coastal nation has diverse social and geographical state, which affected the different impact of mobile adoption on the regional economy. In this study, we address the question on the mobile impact of the economy of 34 provinces in Indonesia by exploiting panel data for the 2009-2017 period with fixed effect model. Finding from our study present evidence the mobile adoption has positive relationships with economic growth especially in low-income per capita region. Moreover, we also found province with higher growth has benefited from more extended education level. Another interesting evidence suggests province with lower economic growth experienced higher income per capita. The government, business and society should consider the finding, especially on ICT development at the regional level.
Keywords: 330; Regional Development; ICT; Mobile adoption; economic growth; fixed effect model; Klassen typology